Social security for dummies - Peterson, Jonathan (Tantor Audio, 2019)
Get the benefits you've earned Social Security For Dummies is the one guide you need to navigate the often-complex world of Social Security retirement benefits. This updated edition offers clear guidance on when to claim benefits, how much you can expect to receive, where to find Social Security calculators, and so much more. Since its inception in the 1930s, workers across the United States have set aside a portion of their wages to fund the Social Security Administration. For many, Social Security forms the foundation for their retirement funds. Social Security For Dummies provides you with all the information you need to take charge of your retirement, maximize your financial well-being, and successfully navigate the U.S. Social Security Administration. You'll get up-to-date information to: &#9679 Make your way around the Social Security website &#9679 Know your Social Security options-including retirement, survivor, spousal, and disability benefits &#9679 Get answers to common questions and find resources when you're stumped Retirement is meant to be enjoyed, and Social Security For Dummies makes it easier.